The Effect of Earnings Per Share (EPS), Earnings Before Interest Taxes Depreciation and Amortization (EBITDA) and Debt to Assets Ratio (DAR) on Stock Prices of PT Sarana Menara Nusantara Tbk for the Period 2010–2024 - Nita Cahyani Gea; Achmad Agus Yasin Fadli (Universitas Dehasen Bengkulu, 2026)
The purpose of this research is to examine the effect of Earnings Per Share (EPS), Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA), and Debt to Assets Ratio (DAR) on stock prices of PT Sarana Menara Nusantara Tbk, located in Kudus, Central Java. This study employs a quantitative research approach. The sampling technique used is saturated sampling, consisting of financial statements of the company over a period of fifteen years, from 2010 to 2024. The data analysis using linear regression analysis. The results indicate that Earnings Per Share (EPS) has a significant effect on stock prices, with a significance value of 0,037 < 0.05 and a t-value of 2,370 > t-table value of 2.201. Meanwhile, Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA) has no significant effect on stock prices, with a significance value of 0,341 > 0.05 and a t-value of -0,995 < 2.201. Likewise, Debt to Assets Ratio (DAR) has significant effect on stock prices, with a significance value of 0,049 > 0.05 and a t-value of 2,638 < 2.201. However, the variables Earnings Per Share, Earnings Before Interest Taxes Depreciation and Amortization , and Debt to Assets Ratio simultaneously have a significant effect on stock prices, as evidenced by a significance value of 0.044 < 0.05 and a calculated F-value of 3,776> F-table value of 3.59.